Compressibilidade de uma argila orgânica mole do Recife - Ferreira, Silvio Romero de Melo (1982)
Compressibility caracteristics of a soft organic clay deposit in the suburb of Madalena, Recife, are studied through consolidation tests with drainage in the vertical direction. A bibliographical review of the geotechnical properties of this clay is presented as well a chemical analysis. An effort is made to answer the following subjects: The deposit’s stress history, the effect of remolding on some compressibility caracteristics, and the coefficient of secondary compression. The non-drained strenght obtained in previous work by other investigators are compared with the non-drained strenght determined through consolidation tests with good quality samples, by means of the equation originally suggested by Mesri (1975): Su = 0,22 δvm, and afterwards developed by Trak et al (1980). The "SHANSEP" Method Ladd and Foot (1974) is also applied using the "CAM-CLAY" model Schofield and Wroth (1968). Finally, the hyperbolical formulation proposed by Kondner (1963) and developed by Duncan and Chang (1970) is used applied to consolidation tests Wong and Chang (1974) for obtaining the initial tengent moduli and numerical moduli of unloading and reloading. By means of these moduli and some hypotheses of work, the specific deformation curve and/or void ratio versus the logarithm of the vertical pressure of consolidation is obtained from the hyperbolical formulation.